"Do you need help?": Dialogics of Change in Community-Based Theatre. Issue 3 (10th August 2016) - Kuftinec, Sonja Arsham
Abstract : It was a hot, sweaty day in Newport News, Virginia, in 1986. Cornerstone Theater's designer, Lynn Jeffries, was building a set for the company's first community-based production, Our Town, cast in part with local participants. Three kids rode up on bikes and drawled, "What y'all doin'?" Jeffries responded that they were building a set for a play, noting that she felt like she was "speaking Chinese." The boys sat for several more minutes. "Do you need help?" And that, according to Jeffries, was "where it all kicked in."